Empathy (Harvard Business Review Press, 2017)
Empathy is credited as a factor in both improved relationships and even better product development. But while it's easy to say, "just put yourself in someone else's shoes," the reality of understanding others' motivations and emotions is more elusive. This book helps you to understand what empathy is, why it's important, how to surmount the hurdles that make you less empathetic--and when too much empathy is just too much.